Intergenerational mobility and sample selection in short panels - Marco Francesconi; Cheti Nicoletti (University of Essex, Institute for Social and Economic Research (ISER), 2004)
Using data from the first eleven waves of the BHPS, this paper measures the extent of the selection bias induced by adulthood and coresidence conditions bias that is expected to be severe in short panels on measures of intergenerational mobility in occupational prestige. We try to limit the impact of other selection biases, such as those induced by labour market restrictions that are typically imposed in intergenerational mobility studies, by using different measures of socioeconomic status that account for missing labour market information. We stress four main results. First, there is evidence of an underestimation of the true intergenerational elasticity, the extent of which ranges between 10 and 25 percent. Second, the proposed methods used to correct for the selection bias seem to be unable to attenuate it, except for the propensity score weighting procedure, which performs well in most circumstances. This result is confirmed both under the assumption of missing-at-random data as well as under the assumption of not-missing-at-random data. Third, the two previous sets of results (direction and extent of the bias, and differential abilities to correct for it) are also robust when we account for measurement error. Fourth, restricting the sample to a period shorter than the eleven waves under analysis leads to a severe sample selection bias. In the cases when the analysis is limited to four waves, this bias may range from 27 to 80 percent.
Keywords: 330